PRACTICAL APPLICATION OF THE PRINCIPLES OF TAX LEGISLATION IN TAX CONTROL - PUHALSKYI, Vadym (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study is devoted to the disclosure of the principles of tax legislation and their role in the tax system and tax control in Ukraine. The principles of tax legislation enshrined in the TCU are not only the basis for the basic principles of taxation (establishment of taxes, their main elements, as well as amendments to certain elements of tax), tax legislation (content and focus of legal regulation of tax relations) in general, but also tax legislation in the field of tax control, in particular. The main purpose of the principles of tax legislation is to ensure a fair tax system in our country, and their strict application will help ensure law and order in the tax area, stability and fairness of the tax system.The author establishes that the principles of tax legislation are special principles of law which are correlated as partial and general.The methodological basis of the study is the scientific developments of domestic scholars on the theoretical and methodological support of the essence, classification and significance of the principles of tax law and tax legislation.The author proves that the principles of tax legislation should be understood as eleven principles of the highest degree of imperative nature which are directly formalized within the provisions of clause 4.1 of Article 4 of the TCU. It is established that these principles are set out in the TCU in a rather concise form.A detailed analysis of the principles of tax legislation in the context of their application in the tax control legislation is made, and the study of the impact of the principles of tax legislation on tax control procedures remains relevant and continues to be the subject of scientific research in the field of tax control.
Keywords: principles; principles of tax law; principles of tax legislation; Tax Code of Ukraine; tax control authorities; taxpayers